2006
DOI: 10.1117/12.689907
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a UV light-emitting diode based fluorescence-phase sensor

Abstract: A set of UV light-emitting diodes (LEDs) with the peak wavelengths ranging from 255 nm to 375 nm was applied for the investigation of spectral and decay-time fluorescence signatures in dry B. globigii spores and common airborne interferants (albuminous, epithelium, and cellulosous materials as well as aromatic hydrocarbons). The fluorescence decay signature was represented by a phase shift of the sinusoidal fluorescence waveform in respect of excitation provided by high-frequency modulated LEDs. The obtained d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…While laboratory fl uorescent lifetime measurement systems are widely available and the concept of lifetime LIF sensing has been demonstrated, 25,26 commercial LIF lifetime sensors are not yet available on the market for PAT and fi eld applications to monitor organic analytes or bioagents. Once available, lifetime LIF sensors could revolutionize fl uorescent based monitoring by affording superior detection merits along with suffi cient recognition power.…”
Section: Light -I Nduced Fl Uoresence ( Lif ) S Ensing C Lassifi Cationmentioning
confidence: 99%
“…While laboratory fl uorescent lifetime measurement systems are widely available and the concept of lifetime LIF sensing has been demonstrated, 25,26 commercial LIF lifetime sensors are not yet available on the market for PAT and fi eld applications to monitor organic analytes or bioagents. Once available, lifetime LIF sensors could revolutionize fl uorescent based monitoring by affording superior detection merits along with suffi cient recognition power.…”
Section: Light -I Nduced Fl Uoresence ( Lif ) S Ensing C Lassifi Cationmentioning
confidence: 99%
“…The phototherapy consists in a reconstruction of the solar spectrum from UVB to visible in order to provide treatment of dermatological (vitiligo and psoriasis) [36,37] sleep and psychiatric disorders [38]. Instead for the plant growth, it was demonstrated that a particular range of wavelength (280-315 nm) [39][40][41][42] increase flowering, nutrition and growth, in addition to a pesticide effect. The biggest problem for the UVB LEDs is the low EQE, that reach in this range values of about 10%, limited from several factors including all the internal, injection and extraction efficiencies.…”
Section: Challenges Of Uv Ledsmentioning
confidence: 99%